Adipose‐derived stromal cell therapy combined with a short course nonmyeloablative conditioning promotes long‐term graft tolerance in vascularized composite allotransplantation. Issue 5 (21st December 2019) - Schweizer, Riccardo; Taddeo, Adriano; Waldner, Matthias; Klein, Holger J.; Fuchs, Nina; Kamat, Pranitha; Targosinski, Stefan; Barth, André A.; Drach, Mathias C.; Gorantla, Vijay S.; Cinelli, Paolo; Plock, Jan A.
Abstract : The risks of chronic immunosuppression limit the utility of vascularized composite allotransplantation (VCA) as a reconstructive option in complex tissue defects. We evaluated a novel, clinically translatable, radiation‐free conditioning protocol that combines anti‐lymphocyte serum (ALS), tacrolimus, and cytotoxic T‐lymphocyte‐associated protein 4 immunoglobulin (CTLA4‐Ig) with adipose‐derived stromal cells (ASCs) to allow VCA survival without long‐term systemic immunosuppression. Full‐mismatched rat hind‐limb‐transplant recipients received tacrolimus (0.5 mg/kg) for 14 days and were assigned to 4 groups: controls (CTRL) received no conditioning; ASC‐group received CTLA4‐Ig (10 mg/kg body weight i.p. postoperative day [POD] 2, 4, 7) and donor ASCs (1 × 10 6 iv, POD 2, 4, 7, 15, 28); the ASC‐cyclophosphamide (CYP)‐group received CTLA4‐Ig, ASC plus cyclophosphamide (50 mg/kg ip, POD 3); the ASC‐ALS‐group received CTLA4‐Ig, ASCs plus ALS (500 µL ip, POD 1, 5). Banff grade III or 120 days were endpoints. ASCs suppressed alloresponse in vitro. Median rejection‐free VCA survival was 28 days in CTRL (n = 7), 34 in ASC (n = 6), and 27.5 in ASC‐CYP (n = 4). In contrast, ASC‐ALS achieved significantly longer, rejection‐free VCA survival in 6/7 animals (86%), with persistent mixed donor‐cell chimerism, and elevated systemic and allograft skin Tregs, with no signs of acute cellular rejection. Taken together, a regimen comprised of short‐course tacrolimus, repeated CTLA4‐Ig and ASC administration, combined with ALS, promotes long‐term VCA survival without chronic immunosuppression. Abstract : A radiation‐free, nonmyeloablative conditioning protocol that combines antilymphocyte serum, tacrolimus, and CTLA4‐Ig with adipose‐derived stromal cells facilitates prolonged, rejection‐free VCA survival without chronic systemic immunosuppression.